Knowing and Growing Hope in Couple Therapy: Perspectives of Couples and Their Therapists - Vriend Fluit, Danielle; Gall, Terry Lynn (Canadian Journal of Counselling and Psychotherapy, 2020)
This study explored experiences of hope shared by couples and their therapists within couple therapy. Four couples and their therapists were interviewed separately. Theme analysis revealed two superordinate themes for couples and therapists: “knowing hope” and “growing hope.” Knowing hope refers to a person’s understanding of hope, while growing hope refers to the experience of hope within the therapy process. Findings revealed that there are similarities and differences in how therapists and couples understand and experience hope. Yet, despite any differences, hope emerges and grows in therapy through a bidirectional process between couples and their therapists.